Examining the Factors that Impact Suicide Following Heterosexual Intimate Partner Homicide: Social Context, Gender Dynamics, and Firearms - Zimmerman, Gregory M. (Journal of interpersonal violence, 2023)
Despite a wealth of research on intimate partner homicide, research on intimate partner homicide followed by suicide of the perpetrator is sparse. Existing studies on intimate partner homicide-suicide: tend to be descriptive, not keeping pace with quantitative advances in the epidemiological and social sciences; have yet to examine how context impacts intimate partner homicide-suicide; and are typically limited to male perpetrators, given small localized samples of female-perpetrated intimate partner (homicide and) homicide-suicide. This study uses data on 7584 heterosexual intimate partner homicide and homicide-suicide cases distributed across 2465 places and 42 U.S. states from the National Violent Death Reporting System (2003–2018) to examine the victim and perpetrator characteristics, relationship dynamics, situational factors, and contextual features that influence the likelihood of committing suicide following intimate partner homicide. Hierarchical logistic regression models indicate that victim characteristics that increase the vulnerability to victimization (alcohol and drug use, mental health problems, less than some college education) decrease the odds of committing suicide following intimate partner homicide. Similarly, situational (victim weapon usage, additional perpetrators) and contextual (concentrated disadvantage, residential instability) risk factors decrease the odds of committing suicide following intimate partner homicide. Conversely, impairment of the perpetrator (alcohol use, mental health problems) and a more intimate victim-perpetrator relationship (spousal relationship, caregiver) increases the odds of homicide-suicide. Additionally, results indicate that firearms play an integral part in homicide-suicide as well as in decreasing the gender gap in homicide-suicide. The findings suggest that the internalization of guilt by perpetrators of intimate partner homicide may play a key role in subsequent suicide. Practically, limiting firearm exposure will not only reduce the lethality of intimate partner violence, but will decrease the odds of perpetrator suicide following intimate partner homicide. This is particularly true for female-perpetrated homicide-suicide, which is unlikely to occur without a firearm.